2015
DOI: 10.5424/fs/2015241-05606
|View full text |Cite
|
Sign up to set email alerts
|

Climate-influenced ponderosa pine (Pinus ponderosa) seed masting trends in western Montana, USA

Abstract: Aim of study: The aim of this study was to analyze 10-year records of ponderosa pine (Pinus ponderosa) seed production, in order to confirm synchronic seed production and to evaluate cyclical masting trends, masting depletion effect, and climate-masting relationships.Area of study: The study area was located in a P. ponderosa stand in the northern Rocky Mountains (western Montana, USA).Material and methods: The study was conducted in one stand that had been subjected to a silvicultural study of uneven-aged man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…5) are consistent with a climate influence on cone initiation (Oliver and Ryker 1990). Keyes and Manso (2015) found that wetter May-August conditions were associated with years of higher cone and seed production in the Northern Rockies, consistent with our finding. Other studies in the Rocky Mountains have linked seasonal climate to cone and seed production, although climate effects on reproduction are highly variable within and between regions (Mooney et al 2011, Keyes andManso 2015).…”
Section: Climate and Post-fire Conifer Regenerationsupporting
confidence: 92%
See 1 more Smart Citation
“…5) are consistent with a climate influence on cone initiation (Oliver and Ryker 1990). Keyes and Manso (2015) found that wetter May-August conditions were associated with years of higher cone and seed production in the Northern Rockies, consistent with our finding. Other studies in the Rocky Mountains have linked seasonal climate to cone and seed production, although climate effects on reproduction are highly variable within and between regions (Mooney et al 2011, Keyes andManso 2015).…”
Section: Climate and Post-fire Conifer Regenerationsupporting
confidence: 92%
“…Other studies in the Rocky Mountains have linked seasonal climate to cone and seed production, although climate effects on reproduction are highly variable within and between regions (Mooney et al. , Keyes and Manso ). In addition, we found warmer‐ and drier‐than‐average conditions three years prior to ponderosa pine regeneration pulses, conditions shown to increase reproductive output and initiate cone production in many conifer species (Owens and Blake , Krannitz and Duralia , Roland et al.…”
Section: Discussionmentioning
confidence: 99%
“…() found that 2‐yr lagged May precipitation and 1‐ and 2‐yr lagged summer temperatures explained 54% of variability in white spruce ( Picea glauca ) seed crops in the Yukon Territory. Keyes and González () observed that seed production in Ponderosa pine ( P. ponderosa ) in Montana was positively correlated with spring temperatures and growing season precipitation. Cain and Shelton () studied seed production for 24 yr in loblolly pine ( Pinus taeda ) and shortleaf pine ( P. echinata ) in the southern United States and found significant positive correlations with summer precipitation 2 yr prior to seed dispersal, and negative correlations with August temperatures 2 yr before seed dispersal; these findings supported similar results reported by Wenger () and Lamb et al.…”
Section: Discussionmentioning
confidence: 99%
“…). Recently, Keyes and González () found evidence for resource depletion in Ponderosa pine ( P. ponderosa ) in Montana over 10 yr of seedfall data, and Funk et al. () observed in Minnesota that bur oak, Q. macrocarpa (a masting species), needed a year to recover from a prescribed burn before producing acorns, whereas pin oak, Q. ellipsoidalis (a non‐masting species), produced acorns the first year after the fire.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change might alter the hydrological cycle in the Mediterranean region (Mariotti et al, 2008), and models predict a reduction in total precipitation and drier summers (Christensen et al, 2007) as well as an increase in fire hazard (Moriondo et al, 2006;Pausas et al, 2008;Moreno et al, 2010). In Mediterranean areas, drought, fire and plant regeneration strategies are closely interlinked (Parra et al, 2012;Orsenigo et al, 2014;Keyes & Manso González, 2015); therefore, knowledge of seed germination of Mediterranean species is a key factor for ecosystem conservation and for directing regeneration efforts (Thomas & Garcia-Marti, 2015).…”
Section: Introductionmentioning
confidence: 99%